Psychometric properties of the Greek version of the Toronto Composite Empathy Scale in Greek dental students. (6th March 2013) - Tsiantou, D.; Lazaridou, D.; Coolidge, T.; Arapostathis, K. N.; Kotsanos, N.
Abstract Introduction Empathy levels of health practitioners are related to patient satisfaction and treatment outcomes. The Toronto Composite Empathy Scale (TCES) was recently developed to assess cognitive and emotional empathy levels in both professional and personal spheres, and tested in an English‐speaking sample of dental students. The aim of this study was to examine the psychometrics of the Greek version of the TCES. Materials and Methods The TCES was translated into Greek and administered to all of the dental students at Aristotle University of Thessaloniki. A random subset of students completed the questionnaire twice for test–retest analysis. Results Nearly all (96.5%) of the students completed the questionnaire. The internal consistencies of each of the four subscales were generally acceptable (Cronbach's alphas: 0.676–0.805), and the scale showed good discriminant and convergent validities (r's for discriminant validity: 0.217 and 0.103; r's for convergent validity: 0.595 and 0.700). Test–retest reliabilities ranged from 0.478 to 0.779. After eliminating items that fell on both cognitive and emotional factors, a rotated factor analysis indicated that the items loaded on two cognitive and three emotional factors. Discussion Our results indicate that the Greek version of the TCES has good psychometric properties. The factor analysis indicates that the emotional and cognitive aspects of empathy are distinct, supporting the need to address both aspects in studies of empathy. Conclusions The Greek version of the TCES is a reliable and valid tool for the measurement of cognitive and emotional empathy, in both professional and personal life, in Greek dental students.